A generalization of the Alzer-Faiziev inequality - Takahasi, Sin-Ei; Miura, Yasuhide (Utilitas Mathematica, 1997)
In this note we give a generalization of the Alzer-Faiziev inequality which sharpenes the classical arithmetic mean and gemetric mean inequality.